PENGARUH KETERLIBATAN KERJA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Badan Pendapatan Daerah Kota Semarang) - Rifki Alan Aldiansyah; Tristiana Rijanti (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2021)
Abstract This study aims to determine the effect of job involvement, motivation, and work environment on employee performance in the Regional_Revenue_Agency of Semarang City. The number of respondents who became the sample in the study were 101 employees_and based on the simple random sampling . The results of the study were analyzed using multiple linear regression with the help of the SPSS 22 program. The results of the analysis show that: (1) Job Involvement has a positive and significant effect on and Employees Employee Performance (2) Motivation has a positive and significant effect on Employee_Performance (3) The Work Environment_has a positive and significant effect on Employees Performance. Keywords : Job Involvement, Motivation, , Work Environment and Employees Performance